THE ASSOCIATION BETWEEN DURATION OF SILICONE OIL TAMPONADE AND RETINAL REDETACHMENT AFTER SILICONE OIL REMOVAL: A SYSTEMATIC REVIEW AND META-ANALYSIS - Andi Arus Victor; Enzo Sapuandi; Raymond Pranata (International Journal of Retina, 2022)
Background: Silicone oil (SO) removal following vitrectomy and injection of silicone oil may cause retinal redetachments (re-RD), with duration of tamponade being considered as the risk factor. So, we wanted to evaluate the duration of silicone oil tamponade as a risk factor of retinal redetachments after silicone oil removal. Result: Ten studies comprising of 2120 eyes were included in this review. Pooled analysis showed no statistically significant difference between the re-RD group and the non-re-RD group in terms of SO duration (mean difference -1.87 months; 95% CI, -3.87 to 0.13; p=0.07; I2=53.1%). The re-RD rate did not differ between the shorter and longer duration of SO tamponade (OR=1.44; 95% CI, 0.54 to 3.82; p=0.47; I2: 63.3%). Conclusion: The duration of SO tamponade was not associated with re-RD after SO removal.